PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (LB3) DITINJAU DARI INDEKS PROPER DI RSUD TUGUREJO SEMARANG - Choidiyah, Siti; Joko, Tri; Setiani, Onny (Fakultas Kesehatan Masyarakat, 2018)
Hospital activities produce a variety of waste, especially hazardous and toxic waste that is harmful to the environment and health, and produce air and water pollution so it is one of the institutions that must perform PROPER. RSUD Tugurejo is a hospital belonging to Central Java which has type B. Hazardous and toxic waste management conducted by RSUD Tugurejo covers sorting, transportation and storage. Hazardous and toxic waste management conducted by RSUD Tugurejo is not in compatible with the technical guideline used, that is the Decree of the Minister of Health No. 1204 of 2004. RSUD Tugurejo has not made a PROPER assessment because it has not been appointed by BLH. The purpose of research was to know hazardous and toxic Waste management in terms of PROPER index at RSUD Tugurejo Semarang. This research is a qualitative research using cross sectional approach. Determination of sample using total sampling consist of 6 main informant and 1 informant triangulation. The results showed that hazardous and toxic waste resulted from 20 service rooms located in RSUD Tugurejo with hazardous and toxic waste total produced daily per day which is 250 Kg. Hazardous and toxic waste management assessment using the Decree of the Minister of Health No. 1204 of 2004 in the form of segmenting, storage, and transportation gets percentage of 52,6% which mean still under standard that is 100%. The results of the assessment of the PROPER index with the hazardous and toxic waste management aspects include the type data collection and the volume of waste and activity reporting, hazardous and toxic waste management permits, permit compliance, the number of hazardous and toxic waste managed, and hazardous and toxic waste management by the 3rd party get the red color index with the percentage of assessment result of 74,1%.